Agricultural Water Allocation under Uncertainty: Redistribution of Water Shortage Risk - Man Li; Xu, Wenchao; Zhu, Tingju (Wiley, 2019)
This article develops an economic model to analyze how the risk of water shortages affects farmers’ land irrigation decision and how the priority-based water sharing arrangement redistributes such a risk among farms with different water rights priorities. The analysis brings together an array of comprehensive data files on irrigation rights, water supplies, and agricultural land use from eastern Idaho. Results indicate that a more left-skewed distribution of streamflow significantly discourages land irrigation among farmers except the most senior rights holders. The priority-based water sharing arrangement redistributes the macroscale risk of water shortages and thus exposes farmers of different water rights priorities to heterogeneous levels of risk: senior water rights holders are affected the least and such a risk is instead passed mostly on to junior water rights holders. The role of water rights in risk redistribution is more significant when the probability distribution of water shortage risk is asymmetric rather than symmetric. The historical development pattern of water rights influences how the priority of water rights takes effect on land irrigation decision.